Characterization of a caffeoyl-CoA O-methyltransferase-like enzyme involved in biosynthesis of polymethoxylated flavones in Citrus reticulata. (17th March 2020) - Liu, Xiaojuan; Zhao, Chenning; Gong, Qin; Wang, Yue; Cao, Jinping; Li, Xian; Grierson, Donald; Sun, Chongde
Abstract: Polymethoxylated flavones (PMFs), which accumulate exclusively in fruit peel of citrus, play important physiological and pharmacological roles but the genetic basis for the methylation of flavonoids has not been fully elucidated in citrus. Here we characterize a caffeoyl-CoA O -methyltransferase-like enzyme, designated CrOMT1. The expression pattern of CrOMT1 was highly correlated with the concentration of the three major PMFs in two different citrus fruit tissues during fruit maturation. Exposure of fruit to UV-B radiation sharply increased the level of CrOMT1 transcripts and also led to the accumulation of three PMFs. The potential role of CrOMT1 was studied by testing the catalytic activity of recombinant CrOMT1 with numerous possible substrates in vitro . The enzyme could most efficiently methylate flavones with neighboring hydroxy moieties, with high catalytic efficiencies found with 6-OH- and 8-OH-containing compounds, preferences that correspond precisely with the essential methylation sites involved in the synthesis of the three naturally occurring PMFs in Citrus reticulata . This indicates that CrOMT1 is capable of in vitro methylation reactions required to synthesize PMFs in vivo . Furthermore, transient overexpression of CrOMT1 increased levels of the three major PMFs in fruit, indicating that CrOMT1 is likely to play an essential role in the biosynthesis of PMFs in citrus. Abstract : Identification of a Citrus reticulata CCoAOMT-like enzyme involved in biosynthesis of polymethoxylated flavones enables further investigation of these secondary metabolites in citrus fruit.